Enhanced performance of GaN-based long-wavelength blue light-emitting diodes with graphene-ITO composite film as transparent conductive electrode - Jinfang Sun; Kan Zhang; Yulong Han; Chengpeng Ni (Materials Research Express, 2023)
We present enhanced performance of GaN-based long-wavelength blue light emitting diodes (LEDs) with hybrid transparent conductive electrodes (TCE) made of graphene and indium tin oxide (ITO) composite. The nearly 100% transmittance TCE were gained when graphene grown by chemical-vapor-deposition was annealed with ITO on the top of it. Compared to conventional LEDs, the work voltage was reduced to 3.5 V at 5 mA forward current. The light emission power was improved about 190%. The good peformance can be attributed to the improved lateral current spreading over the composite graphene-ITO TCE before p-GaN layer injected by carriers.